The Economic Effects of a Borrower Bailout : Evidence from an Emerging Market - Gine, Xavier; Kanz, Martin (World Bank Group, Washington, DC, 2014)
This paper studies the credit market implications and real effects of one the largest borrower bailout programs in history, enacted by the government of India against the backdrop of the 2008-2009 financial crisis. The study finds that the stimulus program had no effect on productivity, wages, or consumption, but led to significant changes in credit allocation and an increase in defaults. Post-program loan performance declines faster in districts with greater exposure to the program, an effect that is not driven by greater risk-taking of banks. Loan defaults become significantly more sensitive to the electoral cycle after the program, suggesting the anticipation of future credit market interventions as an important channel through which moral hazard in loan repayment is intensified.